Jacob Haury, Karl Krumbacher, Otto Adamek und Hermann Braun: Drei Ergänzungen zu Peter Schreiners Edition der Briefe Jacob Haurys an Karl Krumbacher (2006) - Brendel, Raphael (Byzantinische Zeitschrift, 2017)
Three notes on the letters of Jakob Haury to Karl Krumbacher edited by Peter Schreiner: 1. An identification of the book Krumbacher offered to Haury for review. 2. An identification of Braun’s note on textual criticism against which Haury argued. 3. A correction of a misleading typo in Schreiner’s edition.null